A Cultural Shift towards a Sustainable, Bicycle-Oriented Living in Bali - Gusti Ayu Made Suartika; Alexander Cuthbert; Kadek Edi Saputra; Ni Made Swanendri; I Made Agus Dharmadiatmika (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
This paper focuses on the development of a sustainable bicycle-led transport system in Bali. Since the coronavirus pandemic, bicycle use has accelerated globally as a cheap, safe, sustainable and healthy form of transport. But given its global reputation for tourism, Bali is lagging massively behind bicycle transport in more developed economies. So, the paper progresses in five stages. First, the global context for bicycle use is examined. Second, in addition to a more efficient transport system, extraordinary benefits are considered in terms of economic, environmental, societal and human health. Third, due to the lack of prior studies, the Indonesian context is necessarily presented from a seriously constrained data base, and existing legislation. Fourth, the results from an extensive user-focused empirical survey were analyzed. Finally, a series of proposals are suggested for planning policy that would necessarily support bicycle use in Bali.